Differential contribution of dendritic cell CD1d to NKT cell-enhanced humoral immunity and CD8(+) T cell activation - Joshi, Sunil K. (Society for Leukocyte Biology, 2012)
CD1d-restricted type I NKT cells provide help for specific antibody production. B cells, which have captured and presented a T-dependent, antigen-derived peptide on MHC class II and CD1d-binding glycolipid α-GC on CD1d, respectively, activate Th and NKT cells to elicit B cell help. However, the role of the DC CD1d in humoral immunity remains unknown. We therefore constructed mixed bone marrow chimeras containing CD1d-expressing, DTR-transgenic DCs and CD1d(+) or CD1d(−) nontransgenic DCs. Following DT-mediated DC ablation and immunization, we observed that the primary and secondary antibody responses were equivalent in the presence of CD1d(+) and CD1d(−) DCs. In contrast, a total ablation of DCs delayed the primary antibody response. Further experiments revealed that depletion of CD1d(+) DCs blocked in vivo expansion of antigen-specific cytotoxic (CD8(+)) T lymphocytes. These results provide a clear demonstration that although CD1d expression on DCs is essential for NKT-enhanced CD8(+) T cell expansion, it is dispensable for specific antibody production.